Features of the development of modern journalism in terms of the formation of public opinion (Herald of Journalism, 2016)
In this article the author talks about the development of journalism in the new millennium and the new conditions shaping public opinion. The paper presents a concrete analysis of the new journalism, also about its impact on modern society as well as the modern personality. Also listed the pros and cons of the new Widvey Media and projects the possible ways of its development in the future of human society.
Keywords: globalization; national characteristics; V; channel; format; blogger